Ultraperformance liquid chromatography-quadrupole time-of-flight mass spectrometry based untargeted metabolomics to reveal the characteristics of Dictyophora rubrovolvata from different drying methods - Dong, Hui; Zhou, Changyan; Li, Xiaobei; Gu, Haotian; E, Hengchao; Zhang, Yanmei; Zhou, Feng; Zhao, Zhiyong; Fan, Tingting; Lu, Huan; Cai, Min; Zhao, Xiaoyan (Frontiers in Nutrition, 2022)
Dictyophora rubrovolvata is a highly valuable and economically important edible fungus whose nutrition and flavour components may vary based on drying methods. Herein, an untargeted ultraperformance liquid chromatography-quadrupole time-of- flight mass spectrometry (UPLC-Q-TOF/MS) metabolomics method combined with multivariate analysis was first performed to characterize the metabolomics profiles of D. rubrovolvata upon different drying treatments, viz., coal burning drying (CD), electrothermal hot air drying (ED) and freeze drying (FD). The results indicated that 69 differential metabolites were identified, vastly involving lipids, amino acids, nucleotides, organic acids, carbohydrates and their derivatives, of which 13 compounds were confirmed as biomarkers in response to diverse drying treatments. Specifically, most of lipids, such as fatty acyls, glycerophospholipids and sphingolipids, achieved the highest levels in D. rubrovolvata after the CD treatment. ED method substantially enhanced the contents of sterol lipids, nucleotides, organic acids and carbohydrates, while the levels of amino acids, prenol lipids and glycerolipids were elevated dramatically against the FD treatment. The Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis illustrated that differential metabolites were significantly assigned to 59, 55 and 60 pathways of CD vs. ED, CD vs. FD and FD vs. ED groups, respectively, with 9 of the top 20 KEGG pathways shared. Collectively, this study shed light on metabolomic profiles and proposed biomarkers of D. rubrovolvata subjected to multiple drying techniques, which may contribute to quality control and drying efficiency in edible fungi production.